2003
DOI: 10.1211/0022357022610
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of powder formulations for tamp filling processes

Abstract: Tamp filling processes are widely used for the filling of powders into hard gelatin capsules, whereby capsule fill weight is controlled by the formation of a loosely packed plug of material that is dispensed into the capsule shell. To rationally design formulations for tamp filling processes the formulator must have an intimate knowledge of the synergy between machine parameters and powder properties and the corresponding effect on product quality. However, despite ubiquitous use throughout the pharmaceutical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Gelatine can be substituted by other polymeric materials such as 2,4 hypromellose [2, or chitosan when the usage of this material is a social or health issue. [7,8] Loading of powder within such hard capsules is often achieved using the Tamp filling process, [9] which involves the injection of a loosely packed powder plug into the body of capsule, where an intimate knowledge of the synergy between machine parameters, powder properties and lubricant level and their effects on product quality are essential. [9,10] Porous carriers and matrix forming polymers have been combined with drugs to prepare buoyant granular delivery systems, perhaps as alternative to capsules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelatine can be substituted by other polymeric materials such as 2,4 hypromellose [2, or chitosan when the usage of this material is a social or health issue. [7,8] Loading of powder within such hard capsules is often achieved using the Tamp filling process, [9] which involves the injection of a loosely packed powder plug into the body of capsule, where an intimate knowledge of the synergy between machine parameters, powder properties and lubricant level and their effects on product quality are essential. [9,10] Porous carriers and matrix forming polymers have been combined with drugs to prepare buoyant granular delivery systems, perhaps as alternative to capsules.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Loading of powder within such hard capsules is often achieved using the Tamp filling process, [9] which involves the injection of a loosely packed powder plug into the body of capsule, where an intimate knowledge of the synergy between machine parameters, powder properties and lubricant level and their effects on product quality are essential. [9,10] Porous carriers and matrix forming polymers have been combined with drugs to prepare buoyant granular delivery systems, perhaps as alternative to capsules. [11] Floating beads with 34% porosity can provide a two stage drug 426 M. Nangrejo et al release pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Proper powder flow allows uniform particle packing and a constant volume-tomass ratio which maintains capsule weight uniformity and consistent physicomechanical properties of capsule dosage forms [36]. Hardy et al has also reported that the appropriate flow properties of the final blend are necessary to the production of capsules with a consistent fill weight [46].…”
Section: Discussionmentioning
confidence: 99%